10.1001/TESTjama.2012.4607 (CrossRef Listing of Deleted DOIs, 2000)
IMPORTANCE: Industry and federal sponsors support much of the US cancer clinical trial enterprise. Industry-sponsored trials have traditionally focused on therapeutic development and regulatory approval, whereas federally sponsored trials have been viewed as addressing broader clinical and public health research questions. However, differences between these trial portfolios have not been systematically quantified. OBJECTIVE: To characterize differences between federally sponsored and industry-sponsored cancer clinical trials in the US. DESIGN AND SETTING: A comparative study of interventional cancer clinical trial portfolios registered on ClinicalTrials.gov and initiated between 2008 and 2024. US-based interventional cancer trials, including treatment and nontreatment interventions, were included. EXPOSURE: Lead sponsor classified as federal or industry. MAIN OUTCOMES AND MEASURES: Trial characteristics, including study purpose, phase, intervention type, deescalation design, rare cancer focus, and patient age category (adult vs children). Differences in trial characteristics by sponsor type were assessed using χ2 tests and described using odds ratios (ORs) with 95% CIs. RESULTS: Overall, 11 681 federally sponsored trials (n = 2112 [18.1%]) and industry-sponsored trials (n = 9569 [81.9%]) were analyzed. Compared with industry-sponsored trials, federally sponsored trials were less likely to be single-agent drug trials conducted for the purpose of cancer treatment (48.6% vs 77.4%; OR, 0.28; 95% CI, 0.25-0.31; P < .001). In contrast, federally sponsored trials were more likely to evaluate nontreatment interventional trials, including prevention (4.7% vs 1.1%; OR, 4.43; 95% CI, 3.32-5.92; P < .001) and supportive care (2.5% vs 0.9%; OR, 2.92; 95% CI, 2.02-4.20; P < .001). Among trials conducted for the purpose of cancer treatment, federally sponsored studies were more likely to investigate multimodality regimens combining drug and biological agents (19.1% vs 7.4%; OR, 2.98; 95% CI, 2.58-3.44; P < .001) and to combine drug and/or biological agent regimens with radiotherapy (10.5% vs 1.4%; OR, 8.22; 95% CI, 6.51-10.37; P < .001) or surgery (2.5% vs 0.2%; OR, 14.09; 95% CI, 7.95-24.98; P < .001). Federal sponsorship was also associated with greater use of deescalation trial designs (3.1% vs 0.4%; OR, 8.38; 95% CI, 5.43-12.94; P < .001) and trials conducted in rare cancers (17.5% vs 12.1%; OR, 1.54; 95% CI, 1.34-1.77; P < .001) and in children (16.1% vs 5.3%; OR, 3.43; 95% CI, 2.93-4.01; P < .001). CONCLUSIONS: In this study, industry-sponsored trials were more likely to evaluate single-agent drug therapies, whereas US federally sponsored trials were more likely to evaluate nontreatment interventions, multimodality treatment strategies, treatment deescalation approaches, and therapies for rare cancers and pediatric populations. These findings provide an empirical characterization of the complementary and essential roles of federal and industry sponsors in the cancer clinical trial enterprise.